Model Pengembangan Kawasan Wisata Taman Sri Widari Berbasis Tri Hita Karana di Desa Munduk Bestala Buleleng - Ni Made Fani Agustina; Ida Bagus Gede Paramita; Pradna Lagatama (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Taman Sri Widari area (KWTSW) in Munduk Bestala Village has diverse potential for natural, cultural, and man-made tourism. However, this area has not been managed within an integrated and sustainable development model. This research aims to (1) identify the tourism potential in KWTSW that is suitable for development based on Tri Hita Karana; (2) identify supporting and inhibiting factors for development; and (3) design and recommend a development model based on the principles of Tri Hita Karana. This research uses a qualitative approach with case study methods. Data was collected through observation, interviews, and document analysis, and analyzed using the Miles & Huberman model, SWOT analysis, and data triangulation for validation. KWTSW has the potential for spring sources, trekking, bathing pools, and meditation sites. The results can contribute as a reference in designing tourism potential based on local wisdom in KWTSW as it encompasses potential analysis to development models. Internal and external factors are analyzed as the basis for designing the development model. The proposed model is the Ecoculture tourism package of Taman Sri Widari based on Tri Hita Karana, which includes three tourist activities such as bathing in natural pools, trekking, and meditation.